A randomized trial of individualized versus standard of care antiemetic therapy for breast cancer patients at high risk for chemotherapy-induced nausea and vomiting. (December 2020) - Clemons, M.; Dranitsaris, G.; Sienkiewicz, M.; Sehdev, S.; Ng, T.; Robinson, A.; Mates, M.; Hsu, T.; McGee, S.; Freedman, O.; Kumar, V.; Fergusson, D.; et al.
Abstract: Purpose: Despite triple antiemetic therapy use for breast cancer patients receiving emetogenic chemotherapy, nausea remains a clinical challenge. We evaluated adding olanzapine (5 mg) to triple therapy on nausea control in patients at high personal risk of chemotherapy-induced nausea and vomiting (CINV). Methods: This multi-centre, placebo-controlled, double-blind trial randomized breast cancer patients scheduled to receive neo/adjuvant chemotherapy with anthracycline-cyclophosphamide or platinum-based chemotherapy to olanzapine (5 mg, days 1–4) or placebo. Primary endpoint was frequency of self-reported significant nausea, repeated for all cycles of chemotherapy. Secondary endpoints included: duration of nausea, overall total control of CINV, Health Related Quality of Life (HRQoL) using FLIE questionnaire, use of rescue mediation and treatment-related adverse events. Results: 218 eligible patients were randomised to placebo (105) or olanzapine (113). From days 0–5 following each cycle of chemotherapy, 41.3% (95%CI: 36.1–46.7%) of patients in the placebo group reported significant nausea compared to 27.7% (95%CI: 23.2–32.4%) in the olanzapine group (p = 0.001). Across all cycles of chemotherapy, patients receiving olanzapine experienced a statistically significant improvement in HRQoL (p < 0.001). Grade 1/2 sedation was the most commonly side effect reported at 40.8% in the placebo group vs. 54.1% with olanzapine (p < 0.001). Conclusion: In patients at high personal risk of CINV, the addition of olanzapine 5 mg daily to standard antiemetic therapy significantly improves the control of nausea, HRQoL, with no unexpected toxicities. Highlights: Double-blind trial evaluated the addition of olanzapine to triple therapy in patients at high personal risk of CINV. Adding 5 mg olanzapine was associated with significantly improved nausea control with no unexpected toxicities. Olanzapine plus triple therapy should be considered standard of care for breast cancer patients at high risk of CINV.